Theoretical analysis of effective conductivity of metal foams with thermal interface material / Nuurul Syahierah Othman - Nuurul Syahierah, Othman (2018)
Effective thermal conductivity, of six (6) samples of two (2) configurations, between metal foams and thermal interface materials or called TIM, were measured at a maximum force of 45 N (Configuration 1) and 60 N (Configuration 2). The conductivity was measured in order to obtain its analytical value of each configurations or sample and then being compared with the theoretical value. The comparison and results of the test were further explained and discussed as well as the methodology. The TIM tester was developed in house based on ASTM D5470 standard test condition which used to determine the effective thermal conductivity, of thermally conductive solid electrical insulation materials. This tester was used to test all the six (6) samples. Most of the samples showed the trend of increasing conductivity over force applied. However, there is some uncertainty in the value mainly due to improper cooling or performance of the tester itself which discussed more in results and discussions part.